Effect of vanadium content on as-cast micro-structure and mechanical properties of alloy 718. (29th March 2019) - Mo, Yan; Wang, Dongzhe; Liu, Haiding; He, Qubo; Huang, Guoping; Jiang, Bin; Song, Jinhui
Abstract: Effect of limited amounts of vanadium from 0.081 to 1.88 wt% on the micro-structure and mechanical properties in alloy 718 is evaluated. Corresponding morphology, constituent and structure are measured by metallurgical microscope, energy dispersive spectrum, scanning electron microscopy, electron probe micro-analysis and x-ray diffraction. Results indicate that vanadium can refine secondary dendrite arm spacing and decrease segregated spot volume fraction at the investigated levels. Vanadium does not obviously change the precipitated phase composition or structure, but acts as a grain refiner and reduces the precipitated amount of the harmful Laves phase, which results in an optimized as-cast micro-structure for the next homogenization process. In addition, mechanical properties are also tested. They show vanadium may enhance strength to a certain degree. In other words, vanadium altered the micro-structure characteristics of alloy 718 and affected its mechanical properties, and the alloy containing 0.081 wt% vanadium provides the best compromise between strength and micro-structures.